Recruitment of RNA polymerase to Class II CRP-dependent promoters is improved by a second upstream-bound CRP molecule. (25th October 2006) - Miroslavova, N.S.; Mitchell, J.E.; Tebbutt, J.; Busby, S.J.W.
Abstract : Genetics and biochemistry have been exploited to investigate transcription activation by the Escherichia coli CRP (cAMP receptor protein) factor at promoters with a DNA site for CRP near position −41 and the effects of a second upstream-bound CRP molecule. We show that the upstream-bound CRP contributes to transcription activation by improving the recruitment of RNA polymerase.